Minutes of The Governing Council / EC Meeting (Held On 18-10-2013) - Editor, Chief (Indian Journal of Community Health, 2014)
16th IAPSMUPUK State Chapter Annual Conference (18th & 19th October’ 13) Department of Community Medicine, Govt. Medical College, Haldwani, Nainital, Uttarakhand